Pengaruh Kepemimpinan Transformasional dan Kompensasi Terhadap Alstruism Pada PT. Bank Syariah Indonesia KCP Pasuruan Sudirman 1 - Muhammad Ainur Rokan (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
Bank Syariah Indonesia is one of the companies in the banking industry. As a facilitator, Islamic banks play an important role in all economic activities in the halal industry ecosystem. The existence of the Islamic banking industry in Indonesia itself has experienced significant improvement and development in the past three decades. In fact, the spirit to accelerate is also reflected in the number of Islamic banks that take corporate actions. There is no exception for Islamic banks owned by state-owned banks, namely Mandiri Syariah Bank, BNI Syariah, and BRI Syariah. The number of product innovations, service improvements, and network development can be used as benchmarks for the company's success. This study uses a quantitative approach. This article discusses Transformational Leadership, and Compensation for Altruism. Data analysis using multiple linear regression approaches with SPSS 26. Using a sample of 30 respondents by sampling with a Likert scale as a measuring tool. The results of this study are that there is a significant and positive influence between Transformational Leadership and Altruism. Another result of this research shows that Compensation has no effect on Altruism. This study recommends PT. Bank Syariah Indonesia Tbk KCP Pasuruan Sudirman I to further improve aspects of Transformational Leadership, so that employees encourage each other for the development of the company.